Introduction to Mathematical Rigor, MTH 307 Exercises 10 Express each of the following statements as a conditional statement in “if-then” form or as a universally quantified statement. Also write the negation. (a) Every odd number is prime. – (∀x ∈ odd integers ) x is prime. – Negation: (∃x ∈ odd integers ) x is not prime. (b) The sum of the angles of a triangle is 180 degrees. – If x, y, z are the angles of a triangle, then their sum is 180 degrees. – Negation: x, y, z are the angles of a triangle and their sum is not 180 degrees. (c) Passing the test requires solving all the problems. – If you passed the test then you solved all the problems. – Negation: You passed the test and you did not solve all the problems. (d) Being first in line guarantees getting a good seat. – If you are first in line, then you will get a good seat. – Negation: You are first in line and you do not get a good seat. (e) Lockers must be turned in by the last day of class. – (∀x ∈ lockers) x is turned in by last day of class. – Negation: (∃x ∈ lockers ) x is not turned in by the last day of class. (f) Haste makes waste. – (∀x ∈ haste) x makes waste – Negation: (∃x ∈ haste ) x does not make waste. (g) I get mad whenever you do that. – If you do that then I get mad. – Sometimes you do that and I do not get mad. (h) I won’t say that unless I mean it. – If I mean that then I will say that. – Sometimes I won’t say that and I mean that. 31 Which of these statements are believable? (a) (b) (c) (d) “All of my 5-legged dogs can fly.” true “I have no 5-legged dog that cannot fly.” true “Some of my 5-legged dogs cannot fly.” false “I have a 5-legged dog that cannot fly.” false 35 Prove that if x and y are distinct real numbers, then (x + 1)2 = (y + 1)2 if and only if x + y = −2. How does the conclusion change if we allow x = y? 1 Proof: We start with (x + 1)2 = (y + 1)2 . Expanding both sides, we get x2 + 2x + 1 = y 2 + 2y + 1. Cancelling the 1’s and rearranging terms, we get x2 − y 2 = 2y − 2x. We factor each side to get (x + y)(x − y) = 2(y − x) = −2(x − y). As we are given x 6= y, we can divide both sides by x − y to get x + y = −2. As equations preserve equality and these steps are reversible, x + y = −2 implies (x + 1)2 = (y + 1)2 , so the dependence holds both ways. If x can equal y, the statement only holds true when x and y are distinct as before or when x = y = −1. 37 Given a real number x, let A be the statement 1/2 < x < 5/2, let B be the statement x ∈ Z, let C be the statement x2 = 1, and let D be the statement x = 2. Which statements below are true for all x ∈ R. (a) (b) (c) (d) A ⇒ C. False. For a counterexample, let x = 2. B ⇒ C. False. For a counterexample, let x = 2. (A ∧ B) ⇒ C. False. For a counterexample, let x = 2. (A ∧ B) ⇒ (C ∨ D). True. If A and B are true, then x = 1 or x = 2. If x = 1 then C is true. If x = 2 then D is true. So in either case, either C or D is true. (e) C ⇒ (A ∧ B). False. For a counterexample let x = −1. (f) D ⇒ [A ∧ B ∧ (¬C)]. True. If x = 2 then A is true, B is true, and x2 6= 1 so ¬C is true. (g) (A ∨ C) ⇒ B. True. A ∨ C means that x = 1, 2, or −1. So, B is true. 38 Let x, y be integers. Determine the truth value of each statement below. (a) xy is odd if and only if x and y are odd. TRUE. If x is odd and y is odd then x = 2a + 1 for some a and y = 2b + 1 for some b. Then xy = (2a + 1)(2b + 1) = 4ab + 2a + 2b + 1 = 2(2ab + a + b) + 1 which is odd. Suppose it is not true that both x and y are odd. Then at least one is even. Without loss of generality, suppose x is even. Then x = 2a for some a. xy = 2ay which is even. (b) xy is even if and only if x and y are even. FALSE. For a counterexample to the “only if” part, let x = 3 and y = 4. Then, xy = 12 which is even. 2